Change in metabolic parameters and reproductive hormones from baseline to 6-month hormone therapy. Issue 1 (7th January 2022) - Qi, Tongyun; Wang, Xueqing; Huang, Yizhou; Song, Yang; Ma, Linjuan; Ying, Qian; Chatooah, Namratta Devi; Lan, Yibin; Chen, Peiqiong; Xu, Wenxian; Chu, Ketan; Ruan, Fei; et al.
Abstract : Abstract: Adequate evidence showed hormone therapy (HT) reduces the risk of new-onset diabetes in midlife women by decreasing fasting glucose and insulin. However, the improvement of these diabetic biomarkers varied with each individual in clinical observations. The objective of our study was to investigate potential baseline factors associated with the change of fasting glucose and insulin during HT. A retrospective cohort study was performed among 263 midlife participants aged 40 to 60 years with menopausal symptoms who have received 6-month individualized HT. Demographic information and laboratory indicators including reproductive hormone, lipid profiles, diabetic indicators were collected and measured at baseline and were followed-up. A series of statistical analyses were performed to confirm the effectiveness of HT and compare the baseline factors between participants with different glycemic or insulinemic response. Multivariable linear regression model with stepwise variable selection was further used to identify the associated factor with the change of fasting glucose and insulin. Of all participants, fasting glucose ( P = .001) and fasting insulin ( P < .001) were significantly decreased after individualized HT. Significant differences in baseline reproductive hormones were observed in participants with different glycemic response to HT ( P < .001 for both follicle stimulating hormone [FSH] and estradiol). Stepwise linear regression model showed that in addition to baseline fasting glucose levels, baseline FSH was also independently associated with the change of fasting glucose ( β = −0.145, P = .019 for baseline FSH) but not fasting insulin. Greater reduction in fasting glucose in women with higher FSH levels was observed even though they have already been in better metabolic conditions ( P = .037). Midlife women with higher baseline FSH levels have greater reduction in fasting glucose but not fasting insulin. FSH could be an independent predictor of glycemic response to HT in peri- and postmenopausal women.